2019
DOI: 10.3390/su12010004
|View full text |Cite
|
Sign up to set email alerts
|

Vernacular Farm Buildings and Rural Landscape: A Geospatial Approach for Their Integrated Management

Abstract: Over the centuries, farm buildings, which accompany the development of agriculture, have played an important role in defining spatial and environmental planning. In some European countries in particular, these rural structures have been built based on traditional agricultural needs and typical land characteristics. Considering the land abandonment that has occurred over the last five decades, with farmers moving to more comfortable residences in neighboring urban settlements, historical farm buildings have oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 46 publications
(27 reference statements)
0
23
0
Order By: Relevance
“…This is due to the high altimetry in which most of the municipalities of the Basilicata region reside, as highlighted in the research conducted by (Cillis et al, 2019), rural buildings (abandoned or not) in the Basilicata region are found at an average altitude of 500 meters above sea level.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the high altimetry in which most of the municipalities of the Basilicata region reside, as highlighted in the research conducted by (Cillis et al, 2019), rural buildings (abandoned or not) in the Basilicata region are found at an average altitude of 500 meters above sea level.…”
Section: Resultsmentioning
confidence: 99%
“…The more rural the population, the more abundant the rural labor force [61]. The building area plays a crucial role in rural landscapes, reflecting the scale and living standard of rural development [62]; the higher the value, the better the level of rural development. These are all positive indicators.…”
Section: Construction Of the Evaluation Index Systemmentioning
confidence: 99%
“…This interaction has taken shape in both material and immaterial rural culture, for instance, through rural buildings, infrastructures, tools or agricultural techniques. However, global and local drivers of change such as urbanization, rural depopulation, land abandonment, proliferation of industrial agriculture and the introduction of standardized buildings, codes of practice or techniques, have generated an increasing interest in the preservation and management of rural heritage [54,55] and consequently, of the significant part of that heritage that is produced through vernacular processes. This interest is based on multiple socio-cultural, environmental and economic reasons that are often grouped under the overarching goal of sustainable and resilient (rural) development [56,57].…”
Section: About Landscapes and Rural Developmentmentioning
confidence: 99%
“…Additionally, they are a crucial component in the definition of the landscape character, and consequently, there is an increasing research on methodologies to facilitate the consistent analysis, renovation, maintenance and transformation of rural buildings or ethno-villages [54,57]. Additionally, rigorous mapping of vernacular constructions is reported [55], as well as the development of new and deeper interactions between protected rural settlements and the environment by approaching them as complex social-economic-natural systems [58].…”
Section: About Landscapes and Rural Developmentmentioning
confidence: 99%